TINJAUAN YURIDIS TERHADAP HAK KEKAYAAN INTELEKTUAL (HKI) DALAM KEMITRAAN VIRTUAL HOTEL OPERATOR (VHO) - Zeehan Fuad Attamimi; Fadhil Umar (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2022)
The hotel business has developed using a modern cooperation system called the Virtual Hotel Operator (VHO). VHO places its brand name on its partner hotels, so that there is a dualism of brands that can be known by the public, namely the VHO brand and the personal Hotel brand. The purpose of this study is to examine and analyze the juridical property of Intellectual Property Rights (IPR) in the Virtual Hotel Operator (VHO) partnership. This research is a normative juridical method or a doctrinal legal research method, using a statutory and conceptual approach. The form of partnership carried out by Virtual Hotel Operators (VHO) in Indonesia does not contain elements of IPR in it, therefore it needs to be considered because of the consequences of the agreement made by both parties.Keywords: Intellectual Property Rights (IPR), Hospitality Industry, Virtual Hotel Operator (VHO)